Detection of duchene muscular dystrophy carriers with quantitative fluorescent polymerase chain reaction (Annals of Medical Research, 2021)
Aim: Duchenne Muscular Dystrophy (DMD) is an X-linked, progressive, lethal neuromuscular disorder affecting 1/3500 live-born males. Mutations occur in the dystrophin gene, which is located at Xp21.2. Partial gene deletions occur in two “hot-spot” regions, and can be responsible for up to 60-65% DMD cases, while 5-10% of the cases are caused from clustered gene duplications. Mutations can be inherited from female carriers (2/3) or be de-novo mutations (1/3). Deletions can be easily detected in affected males via multiplex PCR or MLPA. On the contrary, determining the status of female carriers is difficult. The aim of this study is to optimize the gene-dosage method using quantitative fluorescent PCR. Material and Methods: Fluorescently labeled primers are used for amplification and automated detection of amplicons and are designed in multiplex format. The primers contain eighteen exons located within “hot-spot” regions. A promoter region and STR markers are also included in the test as internal controls and for linkage analysis. This is followed by a PCR automated genetic analyzer for the detection of PCR products. This study includes twenty-four families, each with a previously diagnosed member.Results: Results showed the same correlation as was previously reported in nineteen patients, whereas three patients had an extra exon deletion and one patient had one less exon deletion than previously reported. In nineteen families, the mothers were carriers, and in five families, the mothers were not carriers. Conclusion: As a conclusion for carrier screening in DMD patients, quantitative fluorescent PCR is a fast, reproducible and robust method can be used for detection of deletions.
Keywords: Duchenne muscular dystrophy; quantitative fluorescent PCR; carrier screening.